2007
DOI: 10.1111/j.1365-2524.1997.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Priorities, “street level bureaucracy” and the community mental health team

Abstract: In the United Kingdom a combination of high profile incidents and reports personally critical of mental health policy in general and individual practitioners' actions in particular (Sheppard 1995) highlight the pressures which operate on mental health professionals in the community (Mechanic 1995a). These pressures are exacerbated by policy contradictions and resource limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 44 publications
1
29
1
Order By: Relevance
“…Organisational and other differences, including the exercise of individual agency [60] and the activities of professionals at 'street level' [61], mean that the consequences of change may not be as intended. Interventions can never truly be trialled or declared as objectively the 'best' approach across all contexts, and evidence and outcomes remain open to differential interpretation.…”
Section: On Problems With Problem Formulation and Waves Of Consequencesmentioning
confidence: 99%
“…Organisational and other differences, including the exercise of individual agency [60] and the activities of professionals at 'street level' [61], mean that the consequences of change may not be as intended. Interventions can never truly be trialled or declared as objectively the 'best' approach across all contexts, and evidence and outcomes remain open to differential interpretation.…”
Section: On Problems With Problem Formulation and Waves Of Consequencesmentioning
confidence: 99%
“…Practice teachers have indicated limited confidence in their legal literacy and argued that the performance indicator and assessment culture in which they work ironically encourages departures from good practice . Similarly, Wells (1997) has also suggested that professional practice and moral responsibility is being compromised by social workers' accountability to their employing agency and by the emphasis on following procedures. Rummery and Glendinning (1999) found that service users' legal entitlements were seriously compromised by organisational procedures.…”
Section: Review Evidencementioning
confidence: 99%
“…Although Michael Lipsky's theory (1980) might still hold some currency in relation to certain groups, in certain contexts (Wells 2007) greater emphasis on top-down management, target setting and care pathways has 'liberated' healthcare professionals from many street level dilemmas.…”
Section: Scandal and Concernmentioning
confidence: 99%